2006
DOI: 10.1002/jcb.20787
|View full text |Cite
|
Sign up to set email alerts
|

1α,25‐dihydroxyvitamin D3‐mediated stimulation of steroid sulphatase activity in myeloid leukaemic cell lines requires VDRnuc‐mediated activation of the RAS/RAF/ERK‐MAP kinase signalling pathway

Abstract: 1Alpha,25-dihydroxyvitamin D(3) (1alpha,25(OH)(2)D(3)) stimulates the activity of steroid sulphatase (STS) in myeloid cells [Hughes et al., 2001, 2005]. This was attenuated by inhibitors of phospholipase D (PLD) (n-butanol, 2,3-diphosphoglyceric acid, C(2)-ceramide) and phosphatidate phosphohydrolase (PAP) (propranolol and chlorpromazine), but was unaffected by inhibitors of phospholipase C. The 1alpha,25(OH)(2)D(3)-induced STS activity was also attenuated by inhibitors of protein kinase Calpha and protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 141 publications
1
39
0
Order By: Relevance
“…Integrin signaling can influence gene expression via ERK activation (5786) and we have shown that blocking activation of ERK1/2 with PD98059 affects osteoblast response to surface microstructure [19]. ERK1/2 also mediates some of the effects of 1α,25(OH) 2 D 3 signaling via ERp60 [20] and others have shown that ERK1/2 participates in responses to 1α, 25(OH) 2 D 3 via the VDR [21]. Thus, by modifying osteoblast differentiation via changes in substrate topography, resulting changes in ERK1/2 may modify the actions of 1α,25 (OH) 2 D 3 through multiple mechanistic pathways.…”
Section: Role Of Integrinsmentioning
confidence: 93%
“…Integrin signaling can influence gene expression via ERK activation (5786) and we have shown that blocking activation of ERK1/2 with PD98059 affects osteoblast response to surface microstructure [19]. ERK1/2 also mediates some of the effects of 1α,25(OH) 2 D 3 signaling via ERp60 [20] and others have shown that ERK1/2 participates in responses to 1α, 25(OH) 2 D 3 via the VDR [21]. Thus, by modifying osteoblast differentiation via changes in substrate topography, resulting changes in ERK1/2 may modify the actions of 1α,25 (OH) 2 D 3 through multiple mechanistic pathways.…”
Section: Role Of Integrinsmentioning
confidence: 93%
“…The activation of Ras/MAPK or the presence of oncogenic Ras was shown to enhance TGF-hinduced epithelial-mesenchymal transition (33,34). More importantly, it has been shown that 1a,25(OH) 2 D 3 regulates the MAPK pathway by activating Ras/RAF-1 signaling in muscle cells and in myeloid leukemic cells (17,18). We showed in this report that the vitamin D 3 analogue Ro3582 increased phosphorylation of Smad1/5 and inhibited cell proliferation in MCF10AT1 cells transfected with Ha-ras, but not in the parent MCF10A cells that lack Ras (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of 1a,25(OH) 2 D 3 and its analogues are mainly mediated through the vitamin D receptor (VDR) or through the membrane-associated signaling pathway (1,15). Membrane-associated responses to 1a,25(OH) 2 D 3 [nongenomic, rapid response to 1a,25(OH) 2 D 3 ], where the mechanism is still unclear, is now considered an essential type of action involved in calcium/phosphate transport, activation of protein kinase C (PKC), and/or the mitogen-activated protein kinase (MAPK) cascade (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 MAPK signaling, along with PI3K/Akt/mTOR, Src kinase, PKC and JAK-STATs are among the major networks that respond to various environmental stimuli and participate in the actions of vitamin D to regulate cell survival, proliferation, differentiation and apoptosis. 7,[14][15][16][17][18][19][20] Several components of MAPK pathways, such as MEKs and ERKs as well as the β-catenin pathway, interact with the classical 1,25D-mediated pathway through direct binding of VDR and then cross-activation of transcription of its target genes. 21,22 Other genes also play key roles in cell differentiation; for instance, the KSR-MAPK-C/EBP pathway is critical to the VDD-induced monocytic differentiation in HL60 cells.…”
mentioning
confidence: 99%